Mathematical modeling of the epidemiology and the transmission dynamics of HIV/AIDS infections in Nigeria (2010)
Many of the already proposed models for the transmission of HIV/AIDS do not fit the situations in Nigeria. This is in part due to the fact that many of the models pay more attention to either homogeneity of sexual contact or population of homosexuals. Although some notable models have also been studied by different authors in times and places for heterosexual transmission of HIV/AIDS epidemics, none of these models addressed the peculiar transmission dynamics in Nigeria. In this study, we grouped the population into susceptible, infected and AIDS men and women with sexual contact as the major route for HIV transmission. Assuming a strong sexual network between the groups and with the AIDS group unable to contribute to infection, we formulated mathematical models for the heterosexual transmission dynamics of HIV/AIDS in Nigeria. Our models incorporated parameters and variables that describe the nature and the strength of the transmission across the groups. We also presented model predictions on pattern of mixing between and Within the groups and how these in turn determine the global dynamics of the epidemics in Nigeria. Our simulation results show that, an increase in the transmission probability as well as in the number of sexual partnership poses more treat to the population than other parameters. The model predictions show that the epidemics tend to level up after year 2010. The number of sexual partners change per year and the probability of an effective contact are among the most critical variables in the HIV/AIDS epidemics in a community of heterosexual Nigerians. Our results agree with recent findings of similar models for some Sub-Saharan African countries. Also, results from the predictions based on the most recent National HIV Seroprevalence Surveillance Survey conducted in Nigeria agree with our findings.